2018
DOI: 10.1001/jamasurg.2017.5025
|View full text |Cite
|
Sign up to set email alerts
|

Seven-Year Weight Trajectories and Health Outcomes in the Longitudinal Assessment of Bariatric Surgery (LABS) Study

Abstract: clinicaltrials.gov Identifier: NCT00465829.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
450
5
13

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 535 publications
(496 citation statements)
references
References 18 publications
28
450
5
13
Order By: Relevance
“…Overall, the trends of individual ADM de‐escalation are consistent with a previous study in the 12 months following BS that showed proportional decreases in each type of ADM . However, we identified a small increase in metformin, sulfonylurea, and insulin from 12 months after BS, which may be due to worsening blood glucose control associated with weight regain …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Overall, the trends of individual ADM de‐escalation are consistent with a previous study in the 12 months following BS that showed proportional decreases in each type of ADM . However, we identified a small increase in metformin, sulfonylurea, and insulin from 12 months after BS, which may be due to worsening blood glucose control associated with weight regain …”
Section: Discussionsupporting
confidence: 89%
“…The likelihood of being off ADM was highest for those who had DS and lowest for those who had LAGB. De‐escalation of ADM may parallel weight loss because LAGB is associated with the least weight loss and DS is associated with the most . Overall, the trends of individual ADM de‐escalation are consistent with a previous study in the 12 months following BS that showed proportional decreases in each type of ADM .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our study’s sample of only 11 SG‐treated participants is too small to draw conclusions about its efficacy. Additional long‐term safety and efficacy data are needed for SG, as was provided for RYGB and LAGB by the Longitudinal Assessment of Bariatric Surgery (LABS) cohort . LABS also provided a more reliable estimate of the risks of adverse perioperative outcomes accompanying RYGB and LAGB, as compared with our small sample (in which some reported AEs were not independently verified).…”
Section: Discussionmentioning
confidence: 99%